AKIBAT HUKUM PUTUSAN PAILIT TERHADAP DEBITOR YANG MELAKUKAN PERJANJIAN PEMISAHAAN HARTA PERKAWINAN - Yoga Adi Putra, Ida Bagus; Novy Purwanto, I Wayan (Kertha Semaya : Journal Ilmu Hukum, 2013)
The paper shall be titled "Legal Consquence of Verdict of Bankrupt Debtors Performing Separation Of Marriage Property Agreement." This paper apply the method of normative analysis method and statutory approach. One of the debtors who could be declared into bankruptcy is a natural person. Recenty, many people married with separation of marital property agreement that also affect settlement or resolution process of the bankruptcy estate belongs to the debtor. Hence it is need to know the position of the husband or wife commated the pre-nuptial agreement in order to resolve uncertainty about the bankruptcy property settlement process.
Keywords: Bankrupt, Legal Consequence Of Verdict, Pre-nuptial Agreement